KOMUNIKASI, PARTISIPASI, DAN KONFLIK DALAM PEMBERDAYAAN MASYARAKAT - Shinta Prastyanti (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2018)
This research aims to analysis the connections among communication, participation, and conflictwithin community empowerment. As we know that community empowerment is not a single activity,but is an ongoing process which is cannot be separated to other variables. Without participation fromall of the stakeholders involved, the community empowerment cannot reach its goal. Thisparticipation gives an open and greater opportunity for all stakeholders to get involved in the process,even to control it. Unfortunately, a greater power for the stakeholder precisely will give anunproductive impact when it correlated to a hidden interest which often tends to give an advantage totheir own group. Furthermore, it cannot be denied if the emerging of conflict which is difficult to besolved. In this part, communication plays an important role to prevent it from that conflict when thereis a mutual understanding among all of the stakeholders. This effective communication will alsocontribute to conflict resolution.